Strategic planning training - Russell, Jeff (Jeffrey Lee); Russell, Linda (ASTD trainer's workshop series., 2005)
"This title is an all-in-one, 'how-to' guide for developing strategic planning, thinking, and decision making competencies of CEOs, managers, supervisors, and frontline employees. It offers a practical set of interactive and customizable learning modules that serve as a roadmap for directing the right framework, culture, and philosophy in your organization. The accompanying CD-ROM includes handouts, checklists, assessments, and customizable PowerPoint(tm) slides."--Publisher's description.